Accessing Minnesota School Administrators’ Knowledge and Perceptions Related to Sharing School Play Spaces after the Passage of Minnesota Shared Use Legislation - Spengler, John; Stasi, Selina (Journal of Healthy Eating and Active Living, 2020)
Lower levels of physical activity among children in the United States can be attributed in part to the lack of access to safe, low-cost recreational facilities. Shared use, or a partnership allowing the community to use school recreational facilities outside of normal hours, has received increased attention. Objective: The objective of this study was to determine the extent of knowledge among school decision makers about a law passed clarifying liability for school shared use in Minnesota and to understand perceptions held by school decision makers regarding shared use of recreational facilities. Design, Setting, and Participants: A survey of Minnesota school superintendents and other decision makers (N = 182) was conducted to understand the issues relevant to sharing school recreational facilities with the public. Results: The majority (90%) of respondents indicated concern about liability for injury on school property outside of normal hours, and that insurance and contracts provided the most protection from liability. Most respondents indicated they were not familiar with the Minnesota shared use legislation and its provisions (61.36%, n = 108). Conclusions: Findings suggest the importance of education and training to further school superintendents’ knowledge of Minnesota shared use legislation, legal and policy issues relevant to shared use, and issues related to the implementation of shared use within their Districts.